Experimental Analysis of Energy Output in Evacuated Tube Heat Pipe Collector with Nanofluids - Desale, Shamkant; Bansod, Premendra; Rachyya, Arakerimath; Campli, Srinidhi (Archives of Thermodynamics, 2026)
Solar heating devices have been extensively investigated to maximise energy utilisation and improve overall thermal efficiency. The present study aims to evaluate the performance of an evacuated tube heat pipe collector with nanofluid and compare it with a conventional heat pipe collector operating without nanofluid, with particular emphasis on the water outlet temperature. In the available literature, several studies have examined the effects of parameters such as the collector inclination angle, nanofluid concentration, and water inlet temperature on the thermal performance of evacuated tube solar collectors. However, a comprehensive comparative analysis incorporating all these parameters on a common experimental platform has not been adequately reported. In the present work, the variation in outlet temperature was systematically analysed by considering independent parameters such as the angle of inclination, copper oxide (CuO) nanofluid concentration, and water inlet temperature. Furthermore, the analysis of variance (ANOVA) was performed on the experimental dataset to evaluate the statistical significance and reliability of the obtained results.